A Systematic Review of Stigma Among Tuberculosis Patient and Its Effect - Nofalia, Ifa; Hariyono, Hariyono; Wibowo, Suhendra Agung; Soamole, Idham; Suharyono, Suharyono; Purnamasari, Ira (International Journal of Psychosocial Rehabilitation, 2020)
The cause of success in the process of treating tuberculosis patients is the emergence of stigma. Stigma has been argued as a barrier to tuberculosis therapy, because, with the stigma, the patient will become more closed, withdrawn and difficult to monitor treatment. The purpose of this systematic review is to determine the stigma among tuberculosis patients and its effect. This study used systematic review with literature search using online reference databases: ProQuest, ScienceDirect and Scopus. The keywords used in this research were tuberculosis OR TB AND social OR public stigma. A full literature search and study selection process was in accordance with the PRISMA guidelines. Studies will be a part of this research if they explain about stigma among tuberculosis patients. The review of 15 articles that met the criteria showed that many tuberculosis patients receive negative stigma in their life. The level of stigma is mostly high. In general, the majority of the community indicated that they would treat TB patients differently for the rest of their lives, do not want those with TB to play with their children, do not want to eat or drink with friends who have TB, and are uncomfortable about being close to those with TB. The stigma among tuberculosis patients is of high rate, so stigma reduction should prioritize the involvement of clients living with the stigmatized condition or behavior and health workers living with stigmatized conditions and should address both individual and structural level stigma.